Management of Neglected Post-traumatic Bilateral Facet Dislocation of Sub-axial Cervical Spine: A Case Series - Marasini, Rudra Prasad (JNMA J Nepal Med Assoc, 2020)
Neglected bilateral facet dislocation of the lower cervical spine is a rare condition and found mostly in developing countries like Nepal. Delayed presentation makes treatment more challenging concerning decompression, reduction, neurological recovery, and overall outcome. We managed three cases of bilateral facet dislocations of the fifth-sixth-seventh cervical vertebra level presented after three months of injury. All of those were treated surgically by combined anterior-posterior-anterior approaches with the same principle. One patient had a complete neurological recovery, the second one recovered partially with few long-term complications and the third one did not improve at all.